Validity of the Science E-Module Based on the 7E Learning Cycle Model Integrated Technological Knowledge - Mustika, Dea; Octa Hadiyanti, Putri; Hidayat, Bahril; Ventari, Ritiya (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2024)
Prospective elementary school teacher students need to understand one of the subjects, namely science, which is taught through the Elementary Science Learning course. In learning, it was found that lecturers dominated lecture activities. Besides, students did not maximize their ability to use technology to find the information. The purpose of the study was to determine the validity of science e-modules based on the 7E Learning Cycle model integrated with technological knowledge. This research is development research using the Plomp development model. The instrument used is an expert validation sheet assessed by 3 validators, namely material validators, language validators, and media validators. The validator's assessment obtained results, namely material experts with 81%, language experts with 88%, and media experts obtained 84%. The overall average of the assessment is 84.3% in the Very Valid category. The conclusion obtained is that the e-module based on the 7E learning cycle model integrated with technological knowledge is valid and feasible to continue for the practicality test.